An Illumina MiSeq sequencing-based method using the mreB gene for high-throughput discrimination of Pseudomonas species in raw milk. (15th June 2022) - Ren, Zeyu; li, Nan; Yu, Leilei; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Zhai, Qixiao
Abstract: Pseudomonas spp. frequently dominate the food spoilage in early cold-chain stage and previous studies suggested the spoliage-related abilities vary in species. Therefore, a species-level method is necessary to clarify the diversity in Pseudomonas spp . In this study, a housekeeping gene ( mreB ) was screened using genomic analysis, which has the ability to distinguish Pseudomonas at species level. Based on this gene, a Pseudomonas -specific primer pair targeting hypervariable region was designed. The primers could specifically distinguish Pseudomonas from other genus but also identify between 142 species in this genus. Using the Illumina MiSeq high-throughput sequencing platform, we proposed a method to rapidly identify Pseudomonas in complex samples and assessed the specificity, accuracy and sensitivity (LOD) of the method. The results showed that this novel approach was reliable and could directly detect as low as 2.648 logCFU/mL of Pseudomonas species. We surveyed the dynamic variation of Pseudomonas at different low temperatures and storage times, different processing points on farms. In conclusion, this method provides a high-throughput sequencing approach to detect more Pseudomonas in susceptible foods material such as milk and meat, which will contribute to analyzing the effect of environmental factor to Pseudomonas community at species level. Highlights: Screen the species-specific gene target of pseudomonas . Establish a high-throughput method to illustrate pseudomonas construction in complex sample such as raw milk. Analyze the dynamic variation of objective microbial community with temperature and time.